Breast mass - An uncommon clinical manifestation of ovarian carcinoma: A case report and brief literature review - Nibedita Sahoo; Mohita Ray; Debahuti Mohapatra; Pallak Batalia (Indian Journal of Pathology and Microbiology)
Metastasis from non-mammary malignant neoplasms to the breast is rare and represents 0.2%-1.3% of all breast malignancies. Fine needle aspiration cytology (FNAC) is the first line of investigation for any breast lump and cyto-morphological appearance of primary breast malignancies is well documented. Occasionally metastasis to the breast may be the initial presentation and can masquerade clinically as primary breast malignancy. The present case describes the clinical and cytological challenges in an unusual case of ovarian carcinoma with initial presentation as breast mass, mimicking as inflammatory carcinoma. In cytology the breast lesion was initially misdiagnosed as primary breast carcinoma and subsequently diagnosed as metastatic ovarian carcinoma based on core needle biopsy findings, aberrant immuno-profile and clinical findings; thus making the complex case worthy of discussion.